The Influence of Teaching Factory Learning on Students’ Entrepreneurial Interest at SMK 2 Pariaman - Mariana Agustina; Ezi Anggraini; Wiwik Gusnita; Naseh Ulwan (Universitas Negeri Padang, 2025)
This study aims to determine the influence of Teaching Factory (TeFa) learning on the entrepreneurial interest of 12th-grade culinary students at SMK Negeri 2 Pariaman. The research employed a causal associative approach. Data were collected through questionnaires distributed to 64 students. Data analysis was conducted using SPSS version 26.0 with a simple linear regression test. The results showed that: (1) Teaching Factory learning was categorized as fairly good (31.25%), and students’ entrepreneurial interest was also in the fairly good category (34.38%). (2) The regression test results indicated a positive and significant influence of TeFa learning on students' entrepreneurial interest, with a significance value of 0.010 (< 0.05). (3) The regression coefficient was 0.350, meaning that each one-unit increase in the TeFa learning variable could increase entrepreneurial interest by 0.350 points. The R Square value was 0.102, indicating that Teaching Factory learning contributed 10.2% to students’ entrepreneurial interest, while the remaining 89.8% was influenced by other factors.